Persepsi mahasiswa fakultas teknologi informasi terhadap pembelajaran daring matematika komputasi pada masa pandemi covid-19 - Febrinita, Filda; Puspitasari, Wahyu Dwi (Jurnal Math Educator Nusantara: Wahana Publikasi Karya Tulis Ilmiah di Bidang Pendidikan Matematika, 2021)
The implementation of online learning in computational mathematics courses has encountered various obstacles in addition to the decline in student learning outcomes. Therefore, research is aimed to explore student perceptions of online learning that has been carried out. The research used a descriptive method with a quantitative approach. The research subjects were students of the Information Technology Faculty of Unisba Blitar who had taken computational mathematics courses during the Covid-19 pandemic. The results showed that students had a positive perception of the aspects of the learning process although some students felt difficulty understanding theory and skills improvement. Positive perceptions are also shown in the competence aspect of lecturers, who become facilitators in the learning process. Furthermore, in the aspect of facilities and infrastructure, positive perceptions are shown in the ease of access to learning materials, the availability of online learning tools and the use of video conferencing in learning. Meanwhile, the negative aspect is shown in the fulfilment of the internet quota for online learning.